2009
DOI: 10.1111/j.1442-2050.2008.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the response to treatment in patients with idiopathic achalasia by the timed barium esophagogram: results from a randomized clinical trial

Abstract: To choose which treatment would be most effective for the individual patient with newly diagnosed achalasia is difficult for the tending physician. A diagnostic tool that would allow prediction of the symptomatic and functional response after treatment for achalasia is therefore needed. The timed barium esophagogram (TBE) is a method that allows objective assessment of esophageal emptying, but the value of TBE in the clinical management of achalasia remains to be clarified. The aim of this study was first, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 28 publications
2
58
0
2
Order By: Relevance
“…Timed barium esophagography has been widely recognized as a simple and objective index of esophageal emptying among patients with achalasia [16,17]. The results from the current study therefore suggest an association between improvement in esophageal emptying and a therapeutic effect on chest pain.…”
Section: Discussionmentioning
confidence: 53%
“…Timed barium esophagography has been widely recognized as a simple and objective index of esophageal emptying among patients with achalasia [16,17]. The results from the current study therefore suggest an association between improvement in esophageal emptying and a therapeutic effect on chest pain.…”
Section: Discussionmentioning
confidence: 53%
“…In a randomized clinical trial of 51 patients who underwent surgery or pneumatic dilation, results of the timed barium esophagogram also correlated well with outcome. Poor improvement in barium height following the treatments was associated with an increased risk of treatment failure [29] .…”
Section: Radiographymentioning
confidence: 99%
“…[24][25][26][27] For objective measurements of efficacy, various parameters can be compared before and after the treatment of achalasia. The objective parameters include barium column height in timed barium esophagograms (TBE), 28,29 LES pressure, integrated relaxation pressure, 30 and GE junction distensibility as measured by EndoFLIP (Endolumenal Functional Lumen Imaging Probe; Crospon, Galway, Ireland). 31 Many studies regarding POEM reported not only subjective clinical symptomatic success, but also objective assessment.…”
Section: Short-term Outcomesmentioning
confidence: 99%